Dual current injection tunable SBG semiconductor laser with asymmetric π equivalent phase shift. Issue 3 (28th January 2013) - Zhou, Yating; Hou, Jie; Chen, Xiangfei
Abstract An asymmetric π equivalent phase shift sampled Bragg grating (SBG) semiconductor, which is consisted of two section with the same length but different sampling duty cycle 0.4 and 0.6, is investigated experimentally. By increasing the two injected currents of the studied laser from 15 mA to 120 mA, the lasing wavelength can be tuned by 2.1 nm. Combining selecting appropriate sampling period, the lasing wavelength of the laser can be tuned to meet the ITU‐T standard. Because of high yield and low cost, this type of SBG laser is very beneficial for designing and fabricating monolithically integrated wideband multiwavelength laser array for photonic integrated circuits in next generation fiber‐optic system. © 2012 Wiley Periodicals, Inc. Microwave Opt Technol Lett 55:692–696, 2013; View this article online at wileyonlinelibrary.com. DOI 10.1002/mop.27357